Pengaruh Strategi Bauran Pemasaran Terhadap Kinerja Pemasaran Dengan Orientasi Kewirausahaan Sebagai Variabel Pemoderasi Pada Uppks (Usaha Peningkatan Pendapatan Keluarga Sejahtera) Di Kota Pekanbaru - Rizal Rahmat; Zulkarnain; Alvi Furwanti Alwie (Jurnal Economica, 2020)
One of the concerns of the government in efforts to reduce poverty is through the BKKBN (National Population and Family Planning Agency), namely by organizing the UPPKS (Prosperous Family Income Improvement Program) program as a family economic empowerment program through the learning of economic businesses by inspiring family interest and enthusiasm for entrepreneurship. UPPKS groups in Pekanbaru City have produced many products that are actually quite attractive and even needed by the community. However, not all UPPKS products are known by the wider community. UPPKS products are mostly made if there are only orders, even though the UPPKS group has the potential to produce products that have a sale value and are mass produced to be sold widely. In the absence of certainty in the amount of production due to the weak marketing strategy, the income received by members of the UPPKS group is unstable, so there is no continuous certainty. The objectives of this research are: To find out and analyze the influence of marketing mix strategies, entrepreneurial orientation and marketing mix which is moderated by entrepreneurial orientation on marketing performance in UPPKS groups in Pekanbaru City. The object of this research was conducted on 29 business groups incorporated in the UPKKS assisted by Pekanbaru City BKKBN. The population in this study were 29 UPPKS groups in Pekanbaru with a total membership of 315 people. Determination of the number of samples was represented by 3 people from each UPPKS group, so the number of samples was 77 people. The data used are primary data through questionnaires. The research analysis tool is Path Analysis with the Multiple Regression Analysis method. The results showed that the marketing mix, and entrepreneurial orientation had a significant effect on marketing performance. The marketing mix strategy if it is moderated by entrepreneurial orientation has a significant influence on marketing performance. Entrepreneurial orientation is an indispensable variable because it can increase the influence of the marketing mix on marketing performance.